Some bilinear inequalities through a weighted Hardy operator - Benaissa, B.; Sarikaya, M.Z. (Carpathian Mathematical Publications, 2025)
In this paper, we give some new generalizations of the bilinear Hardy type inequality by using weighted mean operator S:=Sf_v and its dual S:=Sf_v, where f is a non-negative integrable function with two variables on (0,+∞)×(0,+∞) and v is a weight function.